Reintroduction of native species in an ecological restoration program from a quartzite area of campos rupestres - Carvalho, Aline Cristina; Pereira, Israel Marinho; de Lima, Anderson Oliveira; Zanuncio, José Cola; Rech, André Rodrigo; Kenedy-Siqueira, Walisson; Fernandes, Geraldo Wilson (Plant and soil, 2025)
Background and aims Campo rupestre is an ecosystem in the Espinhaço Mountain Range with high species richness and endemism. The tolerance of Vellozia epidendroides , predominant in this ecosystem, to dehydration seems to facilitate the survival of other plant species. Hence, the importance of V. epidendroides in ecological restoration projects is high. The objective of this study was to evaluate the survival and ecophysiological vegetative performance of V. epidendroides associated with other native species - Apochloa molinioides (Poaceae), Cipocereus minensis (Cactaceae), and Vellozia resinosa (Velloziaceae) - in a project to rescue and reintroduce plants in an area of campo rupestre. Methods Vellozia epidendroides was reintroduced isolated or as the main plant in seven combinations of intercrops with the three other species (seven treatments), randomized in three blocks. V. epidendroides (T1), V. epidendroides + V. resinosa (T2), V. epidendroides + C. minensis + A. molinioides (T3), V. epidendroides + C. minensis (T4), V. epidendroides + V. resinosa + C. minensis (T5), V. epidendroides + V. resinosa + A. molinioides (T6), V. epidendroides + V. resinosa + C. minensis + A. molinioides (T7). Results Overall (all treatments), the survival of V. epidendroides and V. resinosa was 100% and that of C. minensis was 58.3%. The survival of V. epidendroides + C. minensis + A. molinioides , together, was the lowest (66.67%), with all plants of C. minensis dying after 365 days of planting. Shoot emergence was the only ecophysiological performance parameter that varied among treatments, with the highest value for V. epidendroides in T7 when associated with the other three species; V. resinosa associated to V. epidendroides , and C. minensis in the treatment with all four species. Conclusion The reintroduction of species is feasible with V. epidendroides as a companion plant in the reintroduction with the other species, A. molinioides , C. minensis , and V. resinosa , in quartzite areas of campo rupestre. Graphical abstract